PENGARUH DISIPLIN KERJA, LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN TETAP PT. ASUKA ENGINEERING INDONESIA - Syafitri, Maya; Ainul Hidayati, Roziana; Baskoro, Heru (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
This research aims to test the influence of work discipline, work environment and work motivation on the performance of permanent employees of PT. Asuka Engineering Indonesia. This research is research with a quantitative approach. The location of this research is PT. Asuka Engineering Indonesia. The number of samples used in this research was 45 respondents. The sampling technique is nonprobability sampling technique or saturated sampling technique. The analytical technique for testing hypotheses uses the Statistical Package for the Social Sciences (SPSS). The results of the research show that work discipline has a significant effect on employee performance, the work environment has a significant effect on employee performance, and work motivation has a significant effect on employee performance at PT. Asuka Engineering Indonesia.